2021
DOI: 10.3389/fphys.2021.676782
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Inflammation: Insights From High-Altitude Physiology

Abstract: The key regulators of the transcriptional response to hypoxia and inflammation (hypoxia inducible factor, HIF, and nuclear factor-kappa B, NF-κB, respectively) are evolutionarily conserved and share significant crosstalk. Tissues often experience hypoxia and inflammation concurrently at the site of infection or injury due to fluid retention and immune cell recruitment that ultimately reduces the rate of oxygen delivery to tissues. Inflammation can induce activity of HIF-pathway genes, and hypoxia may modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
79
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 169 publications
(217 reference statements)
4
79
0
1
Order By: Relevance
“…Hypoxia-induced inflammation impacts on the immune function and causes chronic disease and high-altitude illnesses [ 5 ]. In the same vein, redox homeostasis has been widely studied as disrupted by hypoxia conditioning [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia-induced inflammation impacts on the immune function and causes chronic disease and high-altitude illnesses [ 5 ]. In the same vein, redox homeostasis has been widely studied as disrupted by hypoxia conditioning [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This prompts the development of alternative interventions to prevent and/or reduce uncontrolled inflammatory response. Although low-intensity, short-term physical activity does not cause significant changes in immunological and physiological responses [9], studies dealing with the role of exercise [10][11][12][13] and relative hypoxic stress exposure [14] demonstrated that muscle-damaging exercise triggers a delayed systemic, predominantly anti-inflammatory, acute cytokine response.…”
Section: Introductionmentioning
confidence: 99%
“…When population reaches the plateau, the cardiomyocytes are subjected to prolonged hypoxic stimulation. Hypoxia will result in the disorder of energy metabolism in cardiomyocytes, accompanied by the accumulation of oxygen free radicals, thus destroying membranous permeability ( 7 ). On the other hand, ventricular hypertrophy is also a distinguishing feature of high-altitude heart disease ( 8 ).…”
Section: Discussionmentioning
confidence: 99%